(3GdYRj aj GdJUQjas - (3GdRfLGfj, YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH, J(B665(3g`s ((3eOQSI YHO Gddg CafOj eMeO CafOjs)
(3ChdgG (B:s
(3GYde Cf GdJUQja aj GddZI GdJZjjQ haj GdUfGYI JMhjd GdCUd GdhGMO Edi CeKdI eNJdaI deYGf ebUhOI dG JMUd EdG HgG Ke GdaYd EeG KdGKj hEeG QHGYj hcd hGMO efgeG EeG eLQO hEeG eRjO ajg hcd hGMO efgeG EeG SGde Ch ZjQ SGdes
(3BNQgG (B:s
(3hGdaYdI HGdcSQ ddfhY ef GdaYd Jbhd gh MSf GdWYeI hGdLdSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 179s
(3eYLe GdeDdajf(B: 1 / 42s
(3cTa GdXfhf(B: 2 / 1138s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas